(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
Uzbekistan is a country with rich opportunities in the development of pomegranate growing and winemaking in a wide range of areas. One of the important tasks is to increase the production of export wines based on the study of the external market and thereby promote the development of our country. This, in turn, requires the training of qualified specialists and workers in the field of winemaking. This article mainly talks about the technology of quality winemaking, types of wine and their positive impact on human life and health. Tips for obtaining high-quality wine products from pomegranates and grapes, the necessary raw materials for winemaking. The following article mainly provides information about the beneficial properties of the pomegranate fruit, its healing properties, the names of the types of wine made from it, and its place in the world market.